Infection with endosymbiotic Spiroplasma disrupts tsetse (Glossina fuscipes fuscipes) metabolic and reproductive homeostasis - Son, Jae Hak; Weiss, Brian L.; Schneider, Daniela I.; Dera, Kiswend-sida M.; Gstottenmayer, Fabian; Opiro, Robert; Echodu, Richard; Saarman, Norah P.; Attardo, Geoffrey M.; Onyango, Maria; Abd-Alla, Adly M. M.; Aksoy, Serap (PLoS pathogens, 2021)
Tsetse flies (Glossina spp.) house a population-dependent assortment of microorganisms that can include pathogenic African trypanosomes and maternally transmitted endosymbiotic bacteria, the latter of which mediate numerous aspects of their host’s metabolic, reproductive, and immune physiologies. One of these endosymbionts, Spiroplasma, was recently discovered to reside within multiple tissues of field captured and laboratory colonized tsetse flies grouped in the Palpalis subgenera. In various arthropods, Spiroplasma induces reproductive abnormalities and pathogen protective phenotypes. In tsetse, Spiroplasma infections also induce a protective phenotype by enhancing the fly’s resistance to infection with trypanosomes. However, the potential impact of Spiroplasma on tsetse’s viviparous reproductive physiology remains unknown. Herein we employed high-throughput RNA sequencing and laboratory-based functional assays to better characterize the association between Spiroplasma and the metabolic and reproductive physiologies of G. fuscipes fuscipes (Gff), a prominent vector of human disease. Using field-captured Gff, we discovered that Spiroplasma infection induces changes of sex-biased gene expression in reproductive tissues that may be critical for tsetse’s reproductive fitness. Using a Gff lab line composed of individuals heterogeneously infected with Spiroplasma, we observed that the bacterium and tsetse host compete for finite nutrients, which negatively impact female fecundity by increasing the length of intrauterine larval development. Additionally, we found that when males are infected with Spiroplasma, the motility of their sperm is compromised following transfer to the female spermatheca. As such, Spiroplasma infections appear to adversely impact male reproductive fitness by decreasing the competitiveness of their sperm. Finally, we determined that the bacterium is maternally transmitted to intrauterine larva at a high frequency, while paternal transmission was also noted in a small number of matings. Taken together, our findings indicate that Spiroplasma exerts a negative impact on tsetse fecundity, an outcome that could be exploited for reducing tsetse population size and thus disease transmission.
Keywords: Infection; Endosymbiotic Spiroplasma; Tsetse (Glossina fuscipes fuscipes) metabolic; Reproductive homeostasis